2013
DOI: 10.2139/ssrn.2637404
|View full text |Cite
|
Sign up to set email alerts
|

Digital Self-Efficacy and Language Learning Enhancement in an Online Setting

Abstract: The importance of personal factors such as personality traits, learning strategies, self-esteem, and self-efficacy in the complicated task of language learning has been established for years. However, the introduction of computers, networks and their wide communication affordances, seem to impact many aspects of learning and teaching and particularly language learning and teaching. The storage place, manner, and magnitude of learning materials for example, have shifted from the human mind to portable digital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The research also indicated that more access to and practice with the Hand phone as a language learning device, enables the students to enjoy the activity and benefit more from a gadget designed primarily for communication and entertainment to enhance their language learning. This in turn, seems to be based on the students' interest in the digital gadgets and their feeling of self-efficacy in using digital devices as new trends in enhancement of language learning (Shakaramia, Khajehei, & Hajhashemi, 2013). The association of students' perceptions of their learning environment with self-efficacy was found to be reasonably strong, indicating that the more skillful students feel in the use of digital devices, the more efficiently they learn if that device is used for the purpose of language learning enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…The research also indicated that more access to and practice with the Hand phone as a language learning device, enables the students to enjoy the activity and benefit more from a gadget designed primarily for communication and entertainment to enhance their language learning. This in turn, seems to be based on the students' interest in the digital gadgets and their feeling of self-efficacy in using digital devices as new trends in enhancement of language learning (Shakaramia, Khajehei, & Hajhashemi, 2013). The association of students' perceptions of their learning environment with self-efficacy was found to be reasonably strong, indicating that the more skillful students feel in the use of digital devices, the more efficiently they learn if that device is used for the purpose of language learning enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…Digital self-efficacy is related to computer self-efficacy that helps in learning activities (Shakarami et al, 2013). Few of the previous research works have used the term internet self-efficacy which means the perceived capability to use the internet (Lai, 2008).…”
Section: Digital Self-efficacymentioning
confidence: 99%
“…He defined it as "the ability to understand and use information in multiple formats from a wide range of digital platforms as required by the new digital age (Glister,1997). Musarrat et al (2018) additionally posit that computer self-efficacy is the user's belief in his ability to perform specific tasks by using multiple digital formats (Shakarami et al, 2013). Computer selfefficacy, as defined in the information technology realm, is the judgement of one's capability to use a computer in performing tasks (Compeau and Higgins, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%